Orofacial strength, dysarthria, and dysphagia in congenital myotonic dystrophy. Issue 3 (10th September 2018) - Berggren, Kiera N.; Hung, Man; Dixon, Melissa M.; Bounsanga, Jerry; Crockett, Becky; Foye, Mary D.; Gu, Yushan; Campbell, Craig; Butterfield, Russell J.; Johnson, Nicholas E.
ABSTRACT: Introduction : Herein we present an exploratory study of orofacial function in children with congenital myotonic dystrophy (CDM) vs. healthy controls. Methods : We evaluated 41 children with CDM and 29 healthy controls for speech and swallow function and for lingual and labial strength. Results : The Iowa Oral Performance Instrument (IOPI), measuring tongue strength, and a lip force meter (LFM), measuring lip strength, had excellent interrater reliability with intraclass correlation coefficients (ICCs) of 0.75 ( n = 19, P < 0.001) and 0.96 ( n = 20, P < 0.001), respectively. Mean overall lingual strength was 3.5‐fold less and labial strength was about 7‐fold less in CDM patients than in healthy controls. Eighteen of 24 children with CDM demonstrated dysarthria and an additional 11 participants were nonverbal. Dysarthria correlated moderately with lingual strength, age, and dysphagia. Strength measures correlated moderately with dysphagia. Discussion : Children with CDM have impaired orofacial functioning that affects communication and swallowing. Reliability of strength measures may be useful for future therapeutic trials. Muscle Nerve 58 : 413–417, 2018